Reed and rush bundle rafts in Ireland - ethnographic and experimental nautical archaeology - Tully, Darina (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
Well into the 20th century, primitive watercraft, constructed of reeds, rushes, and other natural materials, persisted in use in the riverine midland regions of Ireland. While there is no known contemporary photographic evidence of these, some descriptions of various bundle rafts were collected by 19th Century Antiquarians, The Irish Folklore Commission (1935‒1971), and by Folklorists in the Folklife Division of the National Museum. The last two decades have seen a renewed interest in the bundle raft tradition. A literature review was undertaken, known examples were examined, and some basic experimental archaeology was undertaken. The possible use of this archaic form of watercraft in prehistoric Ireland was considered.